Fighting Patton : George S. Patton Jr. through the eyes of his enemies - Yeide, Harry (Zenith Press, 2011)
He is remembered as an officer with few equals. A leader who attained legendary status while commanding corps and armies as a general during World War II. He was also well known for his eccentricity and controversial outspokenness. But no matter the opinion or label attached to his name, few can argue George S. Patton's place as a truly legendary figure in the annals of military history. George S. Patton Jr. was only five years old when he informed his parents he intended to become "a great general." When he learned to read, the first book he bought was a history of decisive battles. In school he was always organizing sham battles. On his honeymoon in France, he took his young bride to historic battlefields and fortresses. Waging war was Patton's passion and all his life he trained himself to fight. Nothing else really mattered to him. Many books have been written about Patton. This is the first to examine the legendary general through the eyes of his enemies, the opposing German commanders. During his ... research through German wartime records, historian and author Harry Yeide has uncovered hundreds of unpublished unit reports, officer accounts, and telephone transcripts to illuminate the German perspective on how and why they lost their battles with Patton's forces. This ... study follows Patton's rise through the ranks in the Mexican Expedition and World War I, as well as his many campaigns throughout World War II, from Tunisia, Sicily and Normandy to Lorraine, the Bulge, and into the heart of Germany.